Chitosan‐functionalized Fe3O4 nanoparticles as an excellent biocompatible nanocarrier for silymarin delivery. (9th June 2021) - Zare, Mahboobeh; Sarkati, Malihe Norouzi
Abstract: Silymarin (SIL) contains a various flavonolignans extracted from Silybum marianum and has an anti‐cancer properties against a variety of cancers. In this study, two types of improved nanocarriers based on iron oxide magnetic nanoparticles (MNPs) including chitosan anchored onto silica coated and uncoated Fe3 O4 MNPs (Cs‐ f ‐SiO2 @Fe3 O4 MNPs and Cs‐ f ‐Fe3 O4 MNPs) were successfully fabricated and characterized. Next, silymarin was loaded into the nanocarriers (SIL‐Cs‐ f‐SiO 2 @Fe3 O4 MNPs and SIL‐Cs‐ f‐ Fe3 O4 MNPs). These systems were characterized and silymarin content, antioxidant activity and intrinsic cytotoxicity were assessed. The functionalization degree of silymarin was assessed by the Folin–Ciocalteu method, finding 120 mg of SIL/g of Cs‐ f ‐SiO2 @Fe3 O4 MNPs and 99 mg of SIL/g of Cs‐MNPs. The antioxidant activity of the silymarin after loading into Cs‐ f‐ SiO2 @Fe3 O4 MNPs and Cs‐ f‐ Fe3 O4 MNPs was proved by DPPH method. These compounds have high antioxidant effect and their radical scavenging activity increased with increasing these concentrations. SIL‐Cs‐ f‐ SiO2 @Fe3 O4 MNPs showed higher antioxidant activity than the SIL‐Cs‐ f ‐Fe3 O4 MNPs in same concentrations. The cytotoxicity of Cs‐ f‐ SiO2 @Fe3 O4 MNPs and SIL‐Cs‐ f‐ SiO2 @Fe3 O4 MNPs against MCF‐7 was investigated by MTT assay and IC50 values were 110.03 and 73.56 μgml −1 respectively. In conclusion, SIL‐loaded MNPs can be used as drug delivery system on target in the treatment of cancer cells.